Whole life sustainability - Ellingham, Ian. ([S.l.] : RIBA Publishing, 2012)
Whole Life Costing (WLC) needs to become a tool in the design process: that is the argument of this new title by Ian Ellingham and William Fawcett. For too long WLC has been misunderstood, considered too complicated for designers to undertake on a readily practical basis. But techniques are changing, and Whole Life Sustainability presents a selection of simple analytical tools that architects can use to arm themselves with confident and qualitative justifications for making sustainable decisions. Increasing numbers of clients are demanding that environmental design is balanced with financial and long-term cost issues, and WLC is a way of finding common currency for making decisions. Whole Life Sustainability shows a number of approaches for doing so, steering clear of number-crunching, and instead using simple 'back-of-the-envelope' techniques, and easy self-assessment tools for the architect to evaluate and understand the whole life of their building. Whole Life Sustainability is a simple route to more insightful, better-quality analysis in the design process.
Keywords: Construction industry--Costs; Life cycle costing; Sustainable design